(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
This article attempts to focus on the issue of human nature in different political stages in Robinson Crusoe with some comparative examples from Gulliver’s Travels and studies individualism and human nature. Moreover, Jonathan Swift’s Gulliver’s Travels, which was written as a satire on human nature in the same period with Robinson Crusoe, also points out and criticizes different emotions in human psychology.